La crisis de la democracia ateniense a través del teatro trágico (Argos, 2025)
The article analyzes three tragedies from the end of the fifth century BC: Oedipus at Colonus, Orestes and Bacchae, proposing that tragic discourse implies a way of thinking of democratic politics. In the context of the crisis suffered by Athens during this period, it is examined how such tragedies explore the problem of stasis as a main aspect of the political situation that characterizes the staging frame in each case. It is assumed that tragic representations of seditious strife made available to the audience thinking resources linked to the circumstances in which the plays were performed.